Overcoming Fundamental Challenges in ELT Classroom - Neupane, Ram Nath (Journal of NELTA Surkhet, 2015)
As English language teachers, we face many challenges in our classroom particularly dealing with mixed ability students, managing classroom discipline, motivating learners, presenting new topics, improving learners’ pronunciation, using appropriate classroom language, encouraging less motivated learners, and dealing with homework. In this light, present article attempts to deal with some of these topics in brief and provides some useful tips to overcome such challenges in the form of reflection of a practicing teacher/ teacher trainer after the references mentioned at the end of this article. Journal of NELTA Surkhet Vol.4 2014: 105-108